Ways to Improve the Current Performance of the Boards of Trustees of Medical Universities in Iran - S Alikhani; M Rahbari; H Farzan; H Aminloo; B Damari (Tehran University of Medical Sciences, 2013)
Background: Establishment of boards of trustees for all universities was legalized in 1988. It is crucial to assess the performance of the boards and to adjust them to the mandates raised by new visions of the country.Methods: Subjects were members of boards of trustees and officers in charge of board's affairs at medical universities. Furthermore, a sample of 860 resolutions adopted by the boards was selected to assess the state of their enforcement.Results: About 70% of the resolutions addressed have been enforced. There is a consensus on focusing on policy-making and high supervision on the objectives of the institutes rather than other areas. Furthermore, ways suggested improving the performance of the boards.Conclusion: Despite the rather high enforcement rate of the resolution in the past ten years, several interventions are suggested to improve the current performance of the boards of trustees and to meet new directions.